Perancangan Buku Ilustrasi Jaranan dengan Teknik Vektor Sebagai Upaya Melestarikan Budaya Lokal Kediri - Prakasa, Aditya Agung; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
Art Jaranan Kediri very thick with each show mystical activities, ranging from trance, to eat things that are not natural, such as eating grass and broken glass. Jaranan Dance Arts is one of art owned by the Indonesian state and  many other cultural arts. In the staging of dance art jaranan tells a brief history jaranan dance arts. Unfortunately at this time, jaranan art like this is now becoming obsolete by youngster. Only generation handful of people who still survive to preserve one of Kediri jaranan dance arts. The lack of information in various media to learn the art of dance jaranan, making dance jaranan Kediri began to fade. Therefore, this study aims to create an illustrated book Jaranan with the vector technique to preserve kediri local culture. The design of this illustrated book using the method of collecting qualitative research method used is by interview, observation, literature study, study competitors, STP studies, and SWOT, which is important in determining the design concept of the study. From the results of the data analysis, the concept of which was obtained was nationalist. Said nationalist taken to create a sense of pride in one of Indonesia's cultural arts. This concept will be used as reference in design, both of illustration, the delivery of the message. Because who else is going to continue and maintain the art if not the next generation, which can trigger the awareness to recognize and preserve our culture. So this jaranan illustrated book with the vector technique is expected to be one of the media that the introduction to children.Keywords: Books Jaranan Kediri, Cartoon Illustration, Preserving Local Culture, Nationalist.